JESKYL – a genetically-improved vaccine to contain pseudorabies disease. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2005)
The vaccine, namely JESKYL, was developed by using a local type of herpesvirus originally obtained from a disease outbreak in Malaysia. The vaccine is proven to be useful to contain the disease, namely pseudorabies that mainly effects swine and some other mammals. Without vaccination, an outbreak of the disease may cause a severe loss to the livestock industry. UPM has successfully developed the vaccine by using an advance biotechnology approach. The safety and the effectiveness ofthe vaccine have been assured following the removal of genetic factors that are responsible for development of viral disease. In the process, two important genes have been removed from the virus or inactivated permanently.